Analisis Semiotika Dalam Puisi “Bunga Gugur” Karya W.S. Rendra - Samsul Maulana Hasanudin (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
Poetry is a literary work that contains meaning written in beautiful words that are aesthetic and expressive. Poetry has a physical and mental structure that can be felt by readers and listeners. Apart from that, in a poetry, there are several markers, either in the form of meaning that needs to be translated by the reader himself or linguistic markers that do not require reinterpretation so that the meaning of the poem will be conveyed from the writer to the reader or listener. The field of study that studies and examines markers, symbols and signals in a field of study is called semiotics. Semiotics is a scientific study that studies the signs in a literary work. Literary activists need to understand semiotics, because a poem definitely contains markers as an aesthetic literary work. Semiotics is very important in providing an overview and understanding of poetry to readers and listeners. That's why semiotics is very important to study and understand, because language and semiotics cannot be separated. The semiotic analysis of the poem "Flower Autumn" has been carried out qualitatively descriptively. Semiotic analysis was carried out on several lines that had words that were interesting to interpret. From the semiotic analysis of the poem "Flower Autumn" by W.S Rendra, readers can conclude that the poem tells the story of a love that is lost when their partner dies.